Campus-industry synergy model to enhance engineering student independence - Rosnelli Rosnelli; Yuniarto Mudjisusatyo; Darwin Darwin (Jurnal Sinar Edukasi, 2025)
Technological developments and the dynamics of the industrial world require universities to produce engineering graduates who are not only academically competent but also independent, adaptive, and ready to face professional challenges. This study aims to examine and develop a model of campus-industry synergy to enhance the independence of engineering students through the integration of project-based learning, industrial internships, and applied research. The research method used was descriptive qualitative, with data collected through interviews, observations, and documentation studies in several engineering study programs at universities that have established active partnerships with industry. The results indicate that campus-industry synergy has a positive impact on improving students' problem-solving abilities, professional responsibility, and managerial skills. Furthermore, industry involvement in curriculum design and student performance evaluation strengthens the relevance of education to the needs of the workforce. Thus, the campus-industry synergy model can be an effective strategy in fostering the independence and competitiveness of engineering graduates in the era of the digital.